Gender and Police Leadership: An Analysis of Metropolitan Police Departments in South Africa - Khosa, Dee (International Journal of Criminology and Sociology, 2021)
Despite a number of initiatives aimed at improving the representation and progressive of women in the law enforcement. Studies continue to document the persistence of gender inequality within law enforcement agencies all over the world and South Africa is not an exception. This article bring to light gender inequalities in the law enforcement sector where women in leadership ranks remains low. Historically, the police career was male-dominated and females were not allowed to work in the police. Therefore, equal gender representation in the workplace should by now be at an advanced developmental stage in South Africa since the abolition of discrimination rules. The Commission on Employment Equity of South Africa reported that women comprised 44.8% of the economically active population, yet males were still in charge of senior management positions in South African industries including the law enforcement environment. The data was collected from female officers from Metropolitan Police departments in Gauteng province. The findings suggest that culture, stereotypes, economic and socio-political dynamics, and physical fitness were perceived as barriers that hindered the representation of women into senior leadership positions.